Efeitos do hipertireoidismo em modelos experimentais de ansiedade, pânico e depressão em ratos. - Nascimento, Monique Pereira do (2010)
Clinical and experimental observations suggest that 2/3 of patients with thyroid disease have psychiatric disorders. However, clinical data are very contradictory. We evaluated the effects of experimental hyperthyroidism produced by administration of L-thyroxine (T4) on indexes of exploratory activity, anxiety, panic and depression of the open field (OF), social interaction (SI), forced swimming (FS), elevated plus-maze (EPM) and elevated T-maze (ETM). Additionally, we evaluated the effects of these treatments on the defensive behaviors induced by electrical stimulation of the dorsal periaqueductal gray (DPAG), a model of panic attack. Male Wistar rats (n = 58) were implanted with electrodes in the DPAG, and five days later, stimulated with pulses of increasing intensities (screening session). Rat that had galloping with intensities below 70 μA were treated for 10 days (i.p.) with saline (controls) or with 30 g/day and 60 g/day of T4 (T30 and T60 groups, respectively). The acute effects on the defense responses of the DPAG were assessed on the the same day of the screening session, and the chronic effects and other tests, after 10 days. Plasma levels of T3 and T4 and the behavioral effects of T4 were evaluated by ANOVA followed by t-tests for independent samples. Response accumulated frequencies of DPAG-evoked behaviors were subjected to the threshold logistic analysis. Differences were considered significant for P <0.05. Although the groups did not differ as to the final weight, they showed similar but significant increases in plasma levels of T3 and T4 in 60% and 50% respectively. In the EPM, there was a significant 12 increase in the percentage of open-arm entry, suggesting an anxiolytic effect. However, indexes of anxiety were not reduced in SI, OF and ETM. These results suggest that the symptom of 'nervousness' reported by 99% of patients with hyperthyroidism is distinct from the anxiety of animal models of this study. However, in the OF test, the T4 increased the rearing, exploration, olfaction and peripheral locomotion, confirming the clinical data of hyperactivity. In contrast, T4 increased the immobility time in FS suggesting a depression-like effect. On the other hand, although the lower dose of T4 reduced the escape latency in the ETM, suggesting a panic-like effect, either the acute or chronic administration of the same dose caused significant increases in the thresholds of immobility, exophthalmus, trotting, galloping and jumping in the model of panic by electrical stimulation of the DPAG, suggesting rather a panicolytic effect. The T60 group also showed significant increases in the thresholds of galloping in both the acute and chronic treatments. Although these data suggest that ETM and DPAG models of panic mobilize different mechanisms, the results were not conclusive regarding the effects of hyperthyroidism in panic attacks, as is often the case in clinical literature. Finally, because animals presented no weight loss, our results suggest that mild hyperthyroidism causes hyperactivity and predisposes individuals to depression